Exploration of Microbial Factories for Synthesis of Nanoparticles – A Sustainable Approach for Bioremediation of Environmental Contaminants - Kapoor, Riti T.; Salvadori, Marcia R.; Rafatullah, Mohd; Siddiqui, Masoom R.; Khan, Moonis A.; Alshareef, Shareefa A. (Frontiers in Microbiology, 2021)
The nanomaterials synthesis is an intensifying research field due to their wide applications. The high surface-to-volume ratio of nanoparticles and quick interaction capacity with different particles make them as an attractive tool in different areas. Conventional physical and chemical procedures for development of metal nanoparticles become outmoded due to extensive production method, energy expenditure and generation of toxic by-products which causes significant risks to the human health and environment. Hence, there is a growing requirement to search substitute, non-expensive, reliable, biocompatible and environmental friendly methods for development of nanoparticles. The nanoparticles synthesis by microorganisms has gained significant interest due to their potential to synthesize nanoparticles in various sizes, shape and composition with different physico-chemical properties. Microbes can be widely applied for nanoparticles production due to easy handling and processing, requirement of low-cost medium such as agro-wastes, simple scaling up, economic viability with the ability of adsorbing and reducing metal ions into nanoparticles through metabolic processes. Biogenic synthesis of nanoparticles offers clean, non-toxic, environmentally benign and sustainable approach in which renewable materials can be used for metal reduction and nanoparticle stabilization. Nanomaterials synthesized through microbes can be used as a pollution abatement tool as they also contain multiple functional groups that can easily target pollutants for efficient bioremediation and promotes environmental cleanup. The objective of the present review is to highlight the significance of micro-organisms like bacteria, actinomycetes, filamentous fungi, yeast, algae and viruses for nanoparticles synthesis and advantages of microbial approaches for elimination of heavy metals, dyes and wastewater treatment.